Teaching English: A Study of Strategy Preferences among Male and Female - Ni Nyoman Ana Yulia Putri; Luh Putu Artini; Dewa Ayu Eka Agustini (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
Various teaching strategies have been applied in English language learning, but there is lack of research in examines how teacher gender influences the preferences of strategies. This lack of knowledge can hinder the development of teaching methods that responsive to individual teacher characteristics. This study identifies differences in teaching strategies between male and female English teachers focusses on the influence of gender on the preferences of teaching methods in the context of Merdeka Curriculum. This tudy aims to describe the teaching strategy preferences used by each gender and understand how these differences can affect the effectiveness of classroom learning. Using a qualitative approach and convenience sampling method, four English teachers (two male and two female) were selected as sample. The data were collected through teaching strategy checklists, observation checklists, interviews, and anecdotal notes, then analyzed using interactive data analysis. The results showed each teacher has different preferences in teaching strategies influenced by students' needs, material needs, and classroom context. The application of various learning strategies can improve the effectiveness of the teaching and learning process. This research is expected to provide more specific recommendations to support the development of teaching methods with students' needs, thus improving the quality of learning.